A roadmap for the implementation of ISO 9001:2000 in academia: 9 steps to certification by FSPP, UiTM. / Maniam Kaliannan and Jasmine Ahmad - Maniam, Kaliannan; Ahmad, Jasmine (Institute of Quality & Knowledge Advancement (InQKA), 2005)
The environment in which universities operate is rapidly becoming demanding, competitive and global. Today, academia faces much the same situation manufacturing and service companies 'in the real world' have been encountering for decades. It seems that only with explicit quality assurance and the ability to operate in a profitable manner will universities be able to survive in the academic market. One of the ways to meet the increasing need for a global quality assurance in academia is to design, implement and maintain quality systems based on the internationally accepted ISO 9000 standards. The Faculty of Administrative Science and Policy Studies (FSPPP), UiTM was awarded ISO 9001: 2000 certification on 11 July 2004. It accomplished this as quickly as possible, spending only six months and less. This paper reveals the timeline and 9 steps FSPPP followed to accomplish its objective. The steps include: 1. Management Commitment, 2. Appointment of Management Representative, 3. Establishment of the ISO 9001:2000 Quality Committee, 4. Implementation Schedule, 5. Draft Quality Documents, 6. Conduct Internal Audit, 7. Respond To Findings, 8. LRQA Adequacy Audit (Stage One) and 9. LRQA Compliance Audit (Stage Two).